andererseits - Yearbook of Transatlantic German Studies Vol. 4, 2015 - Donahue, William Collins; Mein, Georg; Parr, Rolf (andererseits - Yearbook of Transatlantic German Studies, 2016)
andererseits is a collaborative project undertaken by students and faculties of universities in the USA (Duke and the University of Notre Dame), in Luxembourg (University of Luxembourg), and in Germany (University of Duisburg-Essen). It provides a forum for research and reflection on topics related to the German-speaking world and the field of German Studies. Works presented in the publication come from a wide variety of genres including book reviews, poetry, essays, editorials, forum discussions, academic notes, lectures, as well as traditional peer-reviewed academic articles. By publishing such a diverse array of material, we hope to demonstrate the extraordinary value of the humanities in general, and German Studies in particular, on a variety of intellectual and cultural levels. This edition features special sections on the writers Reinhard Jirgl and Barbara Honigmann as well as - for example - essays on Beethoven's 'Heroic New Path', 'Antisemitism in Germany (1890-1933)', the reception of German literature in Great Britain, and a study of post-Wall East German melodrama.